Traître, lâche ou victime ? Le gouverneur d’Exilles face à ses juges (1708-1710) - Paul Vo-Ha (L'Atelier du CRH)
In August 1708, during the War of the Spanish Succession, Laboulaye, the commander of Exilles, surrendered the stonghold he was guarding to the Savoyards after a few days of siege, with the garrison prisoners of war. This quick and suspicious surrender was interpreted by Marshal de Villars as a sign of cowardice, or worse, treason. Faced with the scandal, Laboulaye, eager to defend his honor, requested to be exchanged and went to the Bastille. A lengthy procedure then began, which, 18 months later, resulted in the governor being sentenced to life imprisonment for cowardice, although the charge of treason was ultimately dismissed. This case provides an opportunity to study the social construction process of the coward or traitor, the extraordinary justice set in motion by the royal power to criminalize this hasty surrender, and the public reception of the sentence within the army. In the military sphere, some dissenting voices denounced an unfair judgement, indicating the emergence around this case of a public, or even an autonomous critical public space, that partially emancipated itself from the authorities